Probabilistic power generation expansion planning in a competitive electricity market - Adelino J. C. Pereira (2008)
This paper addresses the generation expansion-planning problem describing a model that generation companies can use to get insight to this problem and to more completely study and characterize different investment decisions. In the last 20 years, the generation activity evolved from a situation in which it was part of vertical companies to unbundled market agents that face a much more risky and uncertain environment. This explains the need to develop this kind of simulation tools to help them building their investment plans as well as analyzing the impact of possible decisions of other players. The simulation model considers a number of possible generation technologies and aims at characterizing the corresponding investment plans from an economic point of view having in mind that market prices, the demand growth, investment and operation costs, as well as other factors, are affected by uncertainties. These uncertainties are modeled by pdf functions and the solution approach uses a Monte Carlo Simulation to sample particular values used to analyse the different investment alternatives from an economic point of view. Finally, the paper presents results from a Case Study illustrating the use of this approach.